2002
DOI: 10.1117/12.475004
|View full text |Cite
|
Sign up to set email alerts
|

<title>Magnetorheological fluids exploiting nanometer-sized particles</title>

Abstract: Magnetorheological(MR) fluids are suspensions of magnetic particles in a carrier fluid. The rheological properties of MR fluids undergo changes on application of magnetic field. MR fluids made using nanometer sized soft magnetic iron particles were studied for their benefits vis-a-vis flow characteristics and settling properties. Three kinds of MR fluids were synthesized using the microwave process (1) 30 µ m sized iron particles (2) 26.5 nm sized iron particle (3) a mixture of micron and nanometer sized iron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…However, with enhancing carrier fluids viscosity, in the presence of a magnetic field, the viscosity of MR materials will be decreased. The second was the use of nano-sized particles to replace micro-sized particles because nano-sized particles may suspend more stable than micro-sized particles in the carrier liquid (John et al, 2002;Laun et al, 1996;Phule and Ginder, 1999;Rosenfeld et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, with enhancing carrier fluids viscosity, in the presence of a magnetic field, the viscosity of MR materials will be decreased. The second was the use of nano-sized particles to replace micro-sized particles because nano-sized particles may suspend more stable than micro-sized particles in the carrier liquid (John et al, 2002;Laun et al, 1996;Phule and Ginder, 1999;Rosenfeld et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Nanometer-sized iron particles, ranging from 10 to 100 nm, were introduced to reduce settling while maintaining useful yield stress levels (Kormann et al, 1992;Taketomi et al, 1993;Rosenfeld et al, 2002). It was shown that the introduction of nanoparticles reduced settling (John et al, 2002;Trihan et al, 2003), but the yield stresses for MR fluids having constant solids loading was reduced when nanoparticles were substituted for micron scale particles in the MR suspension (Poddar et al, 2004;Chaudhuri et al, 2005). However, the shear stresses in these fluids are comparable with shear stresses achieved in conventional electrorheological (ER) fluids and the phenomenon is also seen to be temperature dependent.…”
Section: Introductionmentioning
confidence: 99%